PENGELOLAAN PERIKANAN PUKAT CINCIN BERBASIS BIOEKONOMI MULTISPESIES DI PERAIRAN SELAT SUNDA - Widyanti Octoriani; Mennofatria Boer (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2025)
The Sunda Strait is one of the water areas that has great fisheries potential. Most of the fishermen who fish in the Sunda Strait land their catch at PPP Labuan, Pandeglang Regency. Purse seine is the gear with the largest production volume in Pandeglang Regency. Purse seines catch not only pelagic fish, but also demersal fish and bycatch. Therefore, it is important to analyze fisheries resource management policies using a multispecies approach. The purpose of this research is to determine the dependency relationship and optimal exploitation rate of multispecies caught by purse seines using a multispecies bioeconomic model. The species studied in this research are Fringescale sardinella (Sardinella fimbriata), Indian mackerel (Rastrelliger faughni), Mackerel tuna (Euthynnus affinis), Mackerel (Scomberomorus sp.), and Mackerel scad (Decapterus russelli). The results showed that the relationship between these species is competition and the management of purse seine fisheries has not been running optimally. The regulation of purse seine fishing effort is guided by the MEY (EMEY) fishing effort. The optimal exploitation rate is 236 trips/year. The quota for annual production is 452.87 tons/year for Fringescale sardinella (Sardinella fimbriata), 491.75 tons/year for Indian mackerel (Rastrelliger faughni), 398.68 tons/year for Mackerel tuna (Euthynnus affinis), 370.68 tons/year for Mackerel (Scomberomorus sp.), and 282.25 tons/year for Mackerel scad (Decapterus russelli).